2000
DOI: 10.1128/aem.66.10.4372-4377.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Origin and Community Composition in the Barley Phytosphere as a Function of Habitat and Presowing Conditions

Abstract: An understanding of the factors influencing colonization of the rhizosphere is essential for improved establishment of biocontrol agents. The aim of this study was to determine the origin and composition of bacterial communities in the developing barley (Hordeum vulgare) phytosphere, using denaturing gradient gel electrophoresis (DGGE) analysis of 16S rRNA genes amplified from extracted DNA. Discrete community compositions were identified in the endorhizosphere, rhizoplane, and rhizosphere soil of plants grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 32 publications
2
79
2
3
Order By: Relevance
“…Lopez et al 34 and also Normander and Prosser 42 reported that universal bacterial primers can amplify plant chloroplast rDNA present in samples and therefore repress the PCR amplification of less dominant bacterial populations. It is obvious that amplification of non-target organisms can limit the detection of true bacterial or fungal species because the DNA from non-target organisms competes with the bacterial DNA for primers and deoxynucleoside triphosphates during PCR amplifications.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al 34 and also Normander and Prosser 42 reported that universal bacterial primers can amplify plant chloroplast rDNA present in samples and therefore repress the PCR amplification of less dominant bacterial populations. It is obvious that amplification of non-target organisms can limit the detection of true bacterial or fungal species because the DNA from non-target organisms competes with the bacterial DNA for primers and deoxynucleoside triphosphates during PCR amplifications.…”
Section: Discussionmentioning
confidence: 99%
“…Soil is the main reservoir of the potential bacterial rhizosphere community (Normander and Prosser 2000;De Ridder-Duine et al 2005;Berg and Smalla 2009). Evidence is increasing that plants actively select specific elements of their bacterial rhizosphere microflora, establishing a habitat which is favorable for the plant (Latour et al 1996;Bais et al 2004;Garbeva et al 2004a;Robin et al 2007;Broeckling et al 2008;Houlden et al 2008;Rudrappa et al 2008).…”
Section: Plants Affect Their Microbial Rhizosphere Communitymentioning
confidence: 99%
“…While the origin of phyllosphere bacteria remains poorly defined (Bulgarelli et al 2013), the origins of both endophytic bacteria (Bulgarelli et al 2012;Edwards et al 2015;Long et al 2008;Lundberg et al 2012) and rhizosphere bacteria (Berg and Smalla 2009;Normander and Prosser 2000;Philippot et al 2013;Singh et al 2007) are traditionally thought to be from the soil. Contrary to a soil origin, there is evidence that bacterial endophytes in and/or on maize seeds contribute to the majority of the root endosphere bacterial population (Johnston-Monje et al 2014;JohnstonMonje and Raizada 2011a), and that at least some of these bacteria are able to travel within the plant, exit the roots and colonize the rhizosphere (Johnston-Monje and Raizada 2011a).…”
Section: Introductionmentioning
confidence: 99%